ANALISIS GAYA BAHASA NOVEL SANG PEMIMPI KARYA ANDREA HIRATA SERTA IMPLIKASINYA DALAM PEMBELAJARAN BAHASA SASTRA INDONESIA - Ni Rai Kompyang Dewi Anjani Putri; Ni Luh Sukanadi; Dewa Gede Bambang Erawan (Prodi Pendidikan Bahasa dan Sastra Indonesia FKIP Unmas Denpasar, 2021)
This research is a descriptive study which aims (1) to determine the language style used in Andrea Hirata's novel Sang Pemimpi; (2) This is to determine the implications of the language style of Sang Pemimpi novel in learning Indonesian Language and Literature. Data collection was carried out by reading techniques, recording documents and data reduction. The data in this study were processed using qualitative analysis techniques, namely, the analysis was carried out interactively and continued to completion. The stages in data analysis are data presentation and data analysis. The results of this study indicate that there are 21 types of language styles consisting of 116 language style data. Analysis of the implications of the language style of the novel Sang Pemimpi by Andrea Hirata in Learning Indonesian Language and Literature consists of theoretical implications, pedagogical implications, and practical implications.